Towards a Global View on Suburban Gentrification: From Redevelopment to Development - Delik Hudalah; Nabilla Adharina (Faculty of Geography, Universitas Gadjah Mada, 2019)
The gentrification literature, which is originated in the urban context, has now extended to suburb. Using content analysis on previous related case studies, this article shows that suburban gentrification is not necessarily a natural phenomenon resulting from disinvestment as the neighborhood lifecycle approach commonly suggests. As long as there is a development trigger, the suburb can gentrify anytime as it generally has a lower land value and a lower risk than urban area. The private sector and government play a key role in initiating and facilitating it to happen. In suburban context, the impacts of gentrification is complex, entailing varying negative and positive implications for the physical environment, the economies, and the society.